Body Image and Self-Esteem: The Role of Self in the Third Person Effect Among Female Students at University of Queensland - Yuslikha Kusuma Wardhani Banani (Fakultas Psikologi Universitas Pancasila, 2010)
The present study investigates how the third person effect occurs when one is presented with body images that are stereotypical in the media. It is how perceived negative effect of idealized images on media to self and others related to self esteem. The participants were student of University of Queensland that randomly approached in highly populated area. It has been found that the participants rate negative impact lower for self than for others when they are presented with harmful visual stimulus. However, this study did not support the second hypothesis where there was no significant difference with the participants with high self-esteem and low self-esteem in rating negative impact when they are presented with harmful visual stimulus.